Role of external fields on the nonlinear optical properties of a n-type asymmetric δ -doped double quantum well (2020)
The effects of in-growth applied electric fields and in-plane (x-oriented) magnetic fields on the nonlinear optical rectification (NOR), second harmonic generation (SHG) and third harmonic generation (THG) of n-type asymmetric double δ-doped GaAs quantum well are theoretically investigated. One-dimensional Schrödinger equation is solved by considering effective mass and parabolic band approximations to obtain subband energy levels and their related wave functions. The variations in the NOR, SHG and THG coefficients are determined by using the iterative solutions of the compact density matrix approach. Obtained results indicate that the applied electric field leads to optical red-shift on NOR, SHG and THG coefficients while the magnetic field causes optical blue-shift on that coefficients. Hence we can conclude that applied electromagnetic fields can be used to tune optical properties of devices working within the region of infrared electromagnetic spectrum. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.